Analysis of chosen parts of social insurance in Czech republic and in Slovakia - Korousová, Alice (2011)
The work is concerned with retirement and health insurance. The analysis deal with changes made in legislation of social insurance and it proves effects on state budget. The work involves comparison of analyzed results between Czech republic an Slovak republic.